IMPLEMENTASI HUKUM ISLAM DALAM PEMIKIRAN MU’TAZILAH - Muliati, Muliati (DIKTUM: Jurnal Syariah dan Hukum, 2017)
Abstract: In modern times and the advancement of science and technology, the rational Mutazilah teachings have begun to re-emerge among Muslims especially among the intelectual counity. Unknowingly they have had the same or close understandings of the Mutazila teachings. Having such ideals does not exclude them from Islam.